Mortimer Frank, Johann Ludwig Choulant, and the history of anatomical illustration. (August 2019) - Feibel, Robert M
Mortimer Frank (1874–1919) was an ophthalmologist in Chicago, Illinois. He published a number of papers on the history of medicine, and was secretary of the Chicago Society of the History of Medicine and editor of their Bulletin. His major contribution to the history of medicine relates to the history of anatomical illustration. The classic book on that subject had been published in 1852 in German by the physician and historian, Johann Ludwig Choulant (1791–1861). However, by Frank's time this text was both out dated and out of print. Frank took on the tremendous project of translating Choulant's German text into English as History and Bibliography of Anatomic Illustration in Its Relation to Anatomic Science and The Graphic Arts . He improved Choulant's text with the results of his and other scholars' research, greatly enlarging the text. Frank supplemented the original book with a biography of Choulant, essays on anatomists not considered in the original text, and an essay on the history of anatomical illustration prior to those authors discussed by Choulant. This book, now referred to as Choulant/Frank, has been reprinted several times, and is still useful as a reference in this field, though some of its research is now dated.